2019
DOI: 10.1371/journal.pone.0214124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the spatial distribution of Leishmania parasites in Colombia from clinical samples and human isolates (1999 to 2016)

Abstract: In Colombia, nine species of parasites of the genus Leishmania circulate in more than 20 sand fly species, putting at risk of contracting the disease approximately 60% of the population. The Federico Lleras Acosta Dermatological Center, a reference center in Colombia, has been treating patients with cutaneous and mucosal leishmaniasis for more than 15 years, identifying the infecting Leishmania species from different clinical samples, and recording systematically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 51 publications
1
26
0
1
Order By: Relevance
“…Previous reports of CL outbreaks in Colombia have described higher frequencies of L . panamensis than L. braziliensis , with the latter mainly found in sylvatic environments [ 12 , 52 55 ]. As was found in previous studies, we observed a greater genetic diversity in L. braziliensis than in L. panamensis [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports of CL outbreaks in Colombia have described higher frequencies of L . panamensis than L. braziliensis , with the latter mainly found in sylvatic environments [ 12 , 52 55 ]. As was found in previous studies, we observed a greater genetic diversity in L. braziliensis than in L. panamensis [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…ovallesi (63% L. braziliensis and 73% L. panamensis ) and Lu. gomezi (52% L. braziliensis and 66% L. panamensis ) [ 55 ]. Colombian populations of Pi.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, (iii): migration of animal reservoirs or sand fly vectors responsible for transmission of the parasite within the national territory. L. braziliensis is associated with a wide variety of sand fly vectors (Bejarano et al, 2002;Testa et al, 2002;Ovallos et al, 2013;Ovalle-Bracho et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these findings, knowledge about the genomic variability of L. braziliensis in other South American regions, such as Colombia, is limited. Different studies describe a high frequency of this species in Colombia; this being more frequent in rural (Perez-Franco et al, 2016;Patino et al, 2017) compared with urban populations (Ramirez et al, 2016;Ovalle-Bracho et al, 2019). In addition, Colombia has a large number of sand fly vectors and animal reservoirs, which are involved in the transmission cycle of the parasite (Valderrama-Ardila et al, 2010;Ferro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This fact can be considered reasonable due to the fact that L. panamensis is the etiological agent most frequently reported in Colombia [3,6]. However, recent studies reported that L. braziliensis and L. guyanensis have relevant epidemiological reports and wide spatial distribution in Colombia [68,69]. Considering Colombia as a country with a significant number of pathogenic Leishmania species in circulation, these facts are very critical, bearing in mind that parasite sensitivity to antileishmanial agents relies on Leishmania species [70,71].…”
Section: General Findingsmentioning
confidence: 99%